Wrapped [compact disc, unabridged] - Bradbury, Jennifer (Jennifer A.) (Random House/Listening Library, 2011)
Seventeen-year-old Agnes Wilkins is about to make her debut into 1815 London society at a lavish party, where she meets Lord Showalter, a wealthy and eligible man who collects Egyptian antiquities and who is hiding a dangerous secret.